Active THz metasurfaces for compact isolation - E. Almpanis; G. P. Zouros; K. L. Tsakmakidis (J. Opt. Soc. Am. B, 2021)
Metasurfaces constitute an emerging technology, allowing for compact manipulation of all degrees of freedom of an incident lightwave. A key ongoing challenge in the design of these structures is how to allow for energy-efficient dynamic (active) operation, particularly for the polarization of incident light, which other standard devices typically cannot efficiently act upon. Here, we present a quasi-two-dimensional magneto-optic metasurface capable of simultaneously high-contrast on/off operation, as well as rotation of the polarization angle of a linearly polarized wave—that is, without converting the incident linear polarization to elliptical, which is normally particularly challenging. Furthermore, the device’s operation is broadband, with a bandwidth of around 5 µm, and can be conveniently manipulated using an external magnetic bias. Our findings, corroborated using two different full-wave simulation approaches, may allow for functional metasurfaces operating in the terahertz (THz) regime, giving rise to robust, energy-efficient, and high-dynamic-range broadband isolation, to be used for a wealth of optoelectronic and communication applications.